The Implication of Local Wisdom in Tafsir Al-Azhar on Moderate Islamic Thought by Hamka - Anwar Mujahidin; Hyung-Jun Kim (UIN Maulana Malik Ibrahim Malang, 2021)
The interpretation of the Qur’an as a source of Islamic teachings specifies the character of Islamic thought. The contextual interpretation that acknowledges various socio-cultural realities will generate moderate Islamic thought. This article aims to analyze the relationship between Tafsir al-Azhar by Hamka and Indonesian local wisdom. Tafsir al-Azhar has adopted Indonesian local wisdom as a source of interpretation. The data are derived from the book, Tafsir al-Azhar by Hamka. It describes the forms of local wisdom employed by Hamka as a source of interpretation and maps the implications for moderate Islamic thought in Indonesia. The result of the study shows that the local wisdoms of the archipelago used as a source of interpretation in Tafsir al-Azhar are local community beliefs, community wisdom in dealing with opponents, and community practices on children's education. These local wisdoms are the manifestation of the interpreter’s positive attitude, respecting the noble values of the local community. Respect on the values of local community wisdom is an important finding regarding the contextuality of Qur’an interpretation. The values resulted from the Qur’an interpretation are not coercive but are transferred to society through dialogue, so they reach harmony and peace. Future researches can examine the readers’ response or reception towards Tafsir al-Azhar so that its function to build moderate society can be comprehensively traced. Tafsir al-Qur’an sebagai sumber ajaran Islam menentukan karakter pemikiran Islam. Tafsir al-Qur`an yang kontekstual yang memahami realitas sosial budaya yang beragam akan melahirkan pemikiran Islam yang moderat. Artikel ini bertujuan menganalisis hubungan tafsir al-Azhar karya Hamka dengan kearifan lokal Indonesia. Tafsir al-Azhar telah menggunakan kearifan lokal masyarakat nusantara sebagai sumber penafsiran. Data penelitian bersumber dari tafsir al-Azhar karya Hamka. Tujuan penelitian untuk memaparkan bentuk bentuk kearifan lokal yang digunakan Hamka sebagai sumber penafsiran dan mempetakan implikasinya kepada pemikiran Islam moderat di Indonesia. Hasil penelitian menujukkan bahwa kearifan lokal nusantara yang digunakan sumber penafsiran dalam tafsir al-Azhar meliputi keyakinan masyarakat lokal, kearifan masyarakat menghadapi lawan dan tradisi pendidikan anak. Bentuk-bentuk kearifan lokal tersebut merupakan wujud dari sikap mufassir yang menghargai nilai-nilai luhur masyarakat lokal. Sikap menghargai nilai kearifan masyarakat lokal menjadi temuan penting mengenai kontekstualitas tafsir al-Qur`an. Nilai-nilai yang dihasilkan tafsir al-Qur`an tidak bersifat memaksa tetapi ditransformasikan di masyarakat dengan dialog sehingga tetap terjaga harmoni dan kedamaian. Penelitian ini menyarankan perlunya penelitian resepsi pembaca terhadap tafsir al-Azhar sehingga diketahui secara lebih komprehensi pengaruh moderasi tafsir al-Azhar di masyarakat.